1968
DOI: 10.2466/pr0.1968.23.2.667
|View full text |Cite
|
Sign up to set email alerts
|

An Ontogenetic Study of Electrical Activities in the Cerebral Cortex of the Albino Rat

Abstract: The cortical potentials (EEG) of the albino rat were studied from birth to maturity. For several days after birth the EEG recordings were mostly flat with occasional appearance of 6 to 12 c/s waves of low voltage. After 5 days a long sequence of highly rhythmic waves of the same frequencies was most characteristic, often synchronous with the respiratory cycle and even after gross bodily movement. Frequency of these rhythms increased to 14 to 18 c/s at 14 days. High-voltage slow waves during behavioral sleep ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…1. As this cortical activity was most characteristic of very young rats and first noticed in our previous report (Nagamura and Iwahara, 1968), it was called characteristic rhythmic waves or simply CRW.…”
Section: Eeg Patternsmentioning
confidence: 75%
See 1 more Smart Citation
“…1. As this cortical activity was most characteristic of very young rats and first noticed in our previous report (Nagamura and Iwahara, 1968), it was called characteristic rhythmic waves or simply CRW.…”
Section: Eeg Patternsmentioning
confidence: 75%
“…In a preliminary report from our laboratory, Nagamura and Iwahara (1968) waves of 6-12 Hz on about day 5 from birth, which were often associated with respiratory cycles.…”
mentioning
confidence: 89%
“…activity recorded from the cortex was already reported and has been called "characteristic rhythmic waves (CRW)" (NAGAMURA and IWAHARA, 1968;OISHI and IWAHARA, 1971). In accordance with ADRIAN'S (1950) study with adult rabbits and cats, the rhythmic activity recorded from the OB was considered as "induced" waves caused by room air as an olfactory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…), and (3) the cortical rhythmic activity, appearing in synchrony with the OB induced activity was almost completely abolished (a) when the inspired air was made to by-pass the nasal cavity and (b) after the OB was removed bilaterally. NAGAMURA andIWAHARA (1968) and OISHI andIWAHARA (1971) reported that cortical electrical activity was first recorded 4 to 6 days after birth in postnatal albino rats and usually consisted of highly rhythmic 6-10 Hz waves of low amplitude. As this cortical activity was found characteristic of postnatal rats, it was called "characteristic rhythmic waves (CRW)."…”
mentioning
confidence: 99%